Geometric-phase metalens to be used for tunable optical tweezers in microfluidics - Geromel, René; Rennerich, Roman; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Geometric-phase dielectric meta-lenses made of silicon with high numerical aperture and short focal lengths are fabricated and characterised. For circularly polarised light, the same meta-lens can act as a converging or diverging lens, depending on the handedness of the circular polarisation. This effect enables application for optical tweezers that trap or release µm-size polymer beads floating in a microfluidic channel on demand. An electrically addressable polarisation converter based on liquid crystals may be used to switch between the two states of polarisation, at which the light transmitted through the meta-lens is focused (trapping) or defocussed (releasing), respectively.

Luminescent DNA-origami nano-rods dispersed in a lyotropic chromonic liquid crystal - Zhang, Bingru; Nguyen, Linh; Martens, Kevin; Heuer-Jungemann, Amelie; Philipp, Julian; Kempter, Susanne; Rädler, Joachim O.; Liedl, Tim; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Wolf Schmids Idealgenetisches Modell der narrativen Ebenen im Kontext eines handlungs- und produktionsorientierten Literaturunterrichts - Schulte Eickholt, Swen (Erzähltheorie(n) im Literaturunterricht. Verhandlungen eines schwierigen Verhältnisses)

Fluchterfahrung. Mahi Binebine, Luiz Ruffato und Friedrich Christian Delius im Vergleich - Schulte Eickholt, Swen (Postkoloniale Germanistik und Konflikte im globalen Kontext)

Interkulturelle Konstellationen in Literaturwissenschaft und Literaturdidaktik. Festschrift für Michael Hofmann.

Der Neue Weltengarten. Jahrbuch für Literatur und Interkulturalität 2022

Probleme des Kulturbegriffs der inter und transkulturellen Literaturwissenschaft - Schulte Eickholt, Swen (Interkulturelle Kontellationen in Literaturwissenschaft und Literaturdidaktik. Festschrift für Michael Hofmann)

A Comparison of the Most Intense Periods (MIPs) During Competitive Matches and Training Over an 8-Week Period in a Male Elite Field Hockey Team - Büchel, Daniel; Döring, Michael; Baumeister, Jochen (Journal of Science in Sport and Exercise)
Abstract Purpose Wearables serve to quantify the on-court activity in intermittent sports such as field hockey (FH). Based on objective data, benchmarks can be determined to tailor training intensity and volume. Next to average and accumulated values, the most intense periods (MIPs) during competitive FH matches are of special interest, since these quantify the peak intensities players experience throughout the intermittent matches. The aim of this study was to retrospectively compare peak intensities between training and competition sessions in a male FH team competing in the first german division. Methods Throughout an 8-week in-season period, 372 individual activity datasets (144 datasets from competitive sessions) were recorded using the Polar Team Pro sensor (Kempele, Finland). MIPs were calculated applying a rolling window approach with predefined window length (1–5 min) and calculated for Total distance, High-Intensity-Running distance (> 16 km/h), Sprinting distance (> 20 km/h) and Acceleration load. Significant differences between training and competition MIPs were analysed through non-parametric statistical tests ( P < 0.05). Results Analyses revealed higher MIPs during competition for all considered outcomes ( P < 0.001). Effect size estimation revealed strongest effects for sprinting distance ( d = 1.89 to d = 1.22) and lowest effect sizes for acceleration load ( d = 0.92 to d = 0.49). Conclusion The present findings demonstrate that peak intensities during training do not reach those experienced during competitive sessions in a male FH team. Training routines such as manipulations of court-dimensions and team sizes might contribute to this discrepancy. Coaches should compare training and competition intensities to recalibrate training routines to optimize athletes’ preparation for competition.
Keywords: Nutrition and Dietetics; Rehabilitation; Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; Physiology

KI-basierte Extrahierung von Anforderungen aus Regularien für die Automobilentwicklung - Gräßler, Iris; Özcan, Deniz; Preuß, Daniel (Design fox X - Beiträge zum 34. DfX-Symposium)

Structural fingerprints in the reflectance anisotropy of AlInP(001) - Ruiz Alvarado, Isaac Azahel; Zare Pour, Mohammad Amin; Hannappel, Thomas; Schmidt, Wolf Gero (Physical Review B)